TPACK Based on PjBL Preservice Teachers’s Skill in Developing Digital Economics Teaching Material - Kurniawati, Susanti; Ardiansyah , Hamdan; Sulaeman , Ardika (Jurnal Pendidikan dan Pengajaran, 2024)
This research is motivated by the low skills of teachers in developing digital learning tools, as well as the need for teachers to prepare learning materials that suit the needs of students. In addition, current trainings are still conducted separately and need to be more comprehensive in integrating technology, pedagogy, and content. This study aims to examine the effectiveness of the project-based learning method in improving the skills of developing digital learning tools. This research was conducted using a quantitative and experimental method with a quasi-experiment nonequivalent control group design. With a simple random sampling technique, 90 in-service teachers were obtained. Data collection by observation and test. Instruments are tests and non-tests. Data analysis techniques used one-way anova using the F test and Tukey's Post Hoc. The results of this study state that with the project learning method, there is an increase, especially in the skills of developing learning syntax in teaching modules, producing digital media, compiling digital teaching materials, and developing assessments. The conclusion states that project-based learning can improve the skills of creating digital learning tools in learning economics. This research implies that project-based learning is good for learning aimed at product development and continuous improvement of learning quality.